2019
DOI: 10.11118/actaun201967040973
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cows' Behaviour and Welfare on Dairy Farms in Serbia

Abstract: Modern methods for assessing the welfare of dairy cows are, among other things, often based on the evaluation of animal behaviour. In this regard, behaviour is classified as the most reliable, so‑called animal‑based indicator as its expression comes from the animal itself and indicates a measure in which it has adapted to the environment. Starting from the need to explore the state of welfare and the ability to demonstrate adequate behaviour in dairy farms in Serbia, the Welfare Quality® Assessment Protocol fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
1
1
Order By: Relevance
“…The ease and rapidity of scoring and high intra-and inter-observer repeatability make BCS a widely used herd management tool in bovine practice and scientific research (17). The mean BCS of the breeds (Holstein, Brown Swiss and Simmental) included in the present study was higher than the values previously reported for herds raised in Macedonia, Romania and Serbia, and was close to the value reported for cattle herds raised in Croatia, and revealed that, the criterion 'absence of hunger' was observed at the farm (18)(19)(20)(21). With regard to water supply, the conditions of the assessed farm complied with the minimum standards suggested by the protocol, and the assessment results of the present study showed similarity to those determined in Macedonia and some other countries (1 drinker per 13 animals and 10 l/min) (18)(19)(20)22).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The ease and rapidity of scoring and high intra-and inter-observer repeatability make BCS a widely used herd management tool in bovine practice and scientific research (17). The mean BCS of the breeds (Holstein, Brown Swiss and Simmental) included in the present study was higher than the values previously reported for herds raised in Macedonia, Romania and Serbia, and was close to the value reported for cattle herds raised in Croatia, and revealed that, the criterion 'absence of hunger' was observed at the farm (18)(19)(20)(21). With regard to water supply, the conditions of the assessed farm complied with the minimum standards suggested by the protocol, and the assessment results of the present study showed similarity to those determined in Macedonia and some other countries (1 drinker per 13 animals and 10 l/min) (18)(19)(20)22).…”
Section: Discussionsupporting
confidence: 72%
“…Since the animals were not tethered, it was observed that the bedding material of the parlor, and the resting and walking areas inside and outside the barn were clean and hygienic. In previous research, compared to the present study, higher cleanliness scores and better sanitation were detected in Serbia, Croatia, Romania and the Republic of Macedonia, whereas lower cleanliness scores and poor sanitation were detected in another study performed by the Wye Dairy Research Institute in the United Kingdom (UK) (3,5,6,18,19,22,23).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The selected farms were representative of the Serbian dairy sector, since the vast majority (99.95%) of national agricultural holdings (AHs) specialized in milk production are family-run [38]. In addition, the analyzed farms were characterized by the tie-stall housing system and domestic Simmental dairy breed, which are also prevalent at the national level [39,40].…”
Section: Discussionmentioning
confidence: 99%